2009
DOI: 10.1002/ibd.20771
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Esophagogastroduodenoscopy in Patients with Ileal Pouch–Anal Anastomosis

Abstract: EGD evaluation can yield valuable diagnostic information in selected symptomatic patients with IPAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Hori et al reported the prevalence (19/250: 7.6%) and significant risk factors (pancolitis and a lower dose of predonisolone) of gastroduodenitis-associated UC by performing prospective esophagogastroduodenoscopy for 250 Japanese patients with UC [8]. Since the endoscopic features mimicking those of colon are sometimes helpful for making diagnosis of gastroduodenitis related to UC, EGD is available for examining whether gastroduodenitis would occur in patients with UC after colectomy [9,16]. It was reported that duodenitis associated with UC occurred after colectomy tends to be accompanied by pouchitis as in our present case [9].…”
Section: Discussionmentioning
confidence: 97%
“…Hori et al reported the prevalence (19/250: 7.6%) and significant risk factors (pancolitis and a lower dose of predonisolone) of gastroduodenitis-associated UC by performing prospective esophagogastroduodenoscopy for 250 Japanese patients with UC [8]. Since the endoscopic features mimicking those of colon are sometimes helpful for making diagnosis of gastroduodenitis related to UC, EGD is available for examining whether gastroduodenitis would occur in patients with UC after colectomy [9,16]. It was reported that duodenitis associated with UC occurred after colectomy tends to be accompanied by pouchitis as in our present case [9].…”
Section: Discussionmentioning
confidence: 97%
“…Occasionally, CD may involve other parts of the GI tract. Performance of esophagogastroduodenoscopy with duodenal biopsy [37] and, sometimes, video capsule endoscopy [38] may yield additional information for the accurate diagnosis.…”
Section: Diagnosismentioning
confidence: 99%
“…One study has shown the presence of diffuse duodenitis in some patients with UC [34]. Patients with UC and IPAA have been shown to have evidence of inflammation in the duodenum on endoscopy, as well as histologically [35, 36]. These changes in the proximal small intestine—the site of vitamin D and calcium absorption—can lead to malabsorption and hence vitamin D deficiency.…”
Section: Bone Loss In Patients With Ileal Pouchesmentioning
confidence: 99%